Association of lifestyle-related activity with gestational diabetes mellitus among pregnant women - Sourav, D. G.; Priyanka, A. S.; Tamanna, Tanjeemay; Zaman, Rakib Uz; Moni, Mahfuja Khatun; Suchona, Sadia Haque; Jahan, Nusrat; Tasmia, Khandokar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Gestational diabetes mellitus (GDM) is a significant health concern with complex etiologies involving sociodemographic, lifestyle, and biological factors. This study aimed to explore the relationships between these factors and the risk of GDM in a cohort of pregnant women, with a focus on understanding the impact of lifestyle activities and pre-pregnancy body mass index (BMI). Methods: A case-control study was conducted with 300 pregnant women (150 diagnosed with GDM and 150 healthy controls) at the antenatal clinic of a hospital in Dhaka, Bangladesh. Participants were assessed through detailed questionnaires covering sociodemographic data, obstetric history, and a comprehensive evaluation of lifestyle activities using the pregnancy physical activity questionnaire (PPAQ). Logistic regression analysis was utilized to explore the associations between physical activity levels, pre-pregnancy BMI, and the incidence of GDM. Results: The study found no significant differences in age and bad obstetric history between cases and controls. However, significant disparities in education level and income brackets were observed, with lower education and income levels associated with higher GDM risk. Lifestyle activities showed varying impacts; higher household activity levels unexpectedly correlated with increased GDM risk, while higher levels of sports, exercise, and transportation activities significantly reduced GDM risk. Additionally, a higher pre-pregnancy BMI was strongly associated with increased GDM risk. Conclusions: The study highlights the influence of socioeconomic factors and lifestyle activities on GDM risk, demonstrating that both higher physical activity levels and maintaining a normal pre-pregnancy BMI are pivotal in reducing GDM incidence. These findings suggest that interventions aimed at enhancing lifestyle modifications and addressing socioeconomic barriers could be effective in mitigating GDM risk among pregnant women.